The Role of Audit Committee Supervision on Integrated Reporting Relationship and Firm Value - Zaky Machmuddah; Anna Sumaryati; Muchammad Syafrudin (Pusat P2M Politeknik Negeri Batam, 2022)
This study aims to find empirical evidence of the role of the audit committee and audit committee activities in moderating the effect of integrated reporting on firm value. WarpPLS version 7.0 is used as an analytical tool by using a sample of manufacturing companies listed on the Indonesian stock exchange for five years of observation, from 2016 to 2020, to obtain 150 observational data. The results of the study indicate that integrated reporting influences firm value. Likewise, the role of the audit committee and the activities of the audit committee, as proxied by the number of audit committee meetings, moderated the effect of integrated reporting on firm value. The limitation of this research is that the value of R2 is still low at 22%. Therefore, it is still possible to modify this research by changing the research variables used for further study. The implication of this research is the importance of the supervisory role of the audit committee in implementing integrated reporting to increase firm value.